ANALISIS PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI MANUFAKTUR DI PROVINSI JAWA TIMUR - Mahyastiwi, Dinar Karinenna; murgianto, murgianto (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
The purpose of this study is to determine whether there is an effect of the manufacturing sector and the minimum wage on labor absorption in East Java Province in 2012-2018. This research data use secondary time series data from 2012-2018 obtained from the BPS and other related agencies. This type of research is quantitative. From the results of research that has been conducted by the author that the manufacturing industry sector has a partially significant positive effect on employment in East Java Province. The results of this study have a significance of 0,000 < 0,05 and the minimum wage has a partial negative effect on labor absorption in East Java Province. The results of this study have a significance value of 0,016 < 0,05. While the determination test has an effect of 99,5% of the independent variables and the remaining 0,005% of the variation the dependent variable is explained by variables outside the independent variables of this study. The conclusion in this study is that the manufacturing industry and the minimum wage together affect labor absorption in East Java Province. Suggestions were given to the Government to increase investment in the manufacturing sector, which absorbs a lot of labor and reduces the minimum wage level so that employment opportunities can increase.